Therapeutic Management of Corneal Ulceration in a Pug: A Case Report - Verma, Prashant; Arora, Niddhi; Kalita, Jyoti Chanda; Prasad, Amit; Singh, Anand Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Corneal ulceration refers to corneal infiltration coupled with an adjacent epithelial defect and is one of the most frequent conditions of eye seen in small-animal medicine which is regarded as a major cause of blindness in dogs, either due to severe scarring or following corneal dehiscence (Ibrahim et al., 2009; Startup, 1984). In a study it was estimated that corneal ulcer accounted for 16.81% of cases presented with ocular affections and pug breed of dog had highest level of affection with corneal ulcer (Patel et al., 2020). Corneal ulcer may develop as a consequence of variety of aetiologies which includes trauma, irritants, tear film defects, abnormalities of eyelids, foreign bodies and others (Packer et al.,2015). These etiological agents produce varied clinical signs in dogs which includes corneal oedema, excessive tear formation in eye, construction of pupil, blepharospasm, protrusion of nictitating membranes, redness of conjunctiva and photophobia (Belknap, 2015). Diagnosing corneal ulcers requires diagnostic techniques such as fluorescein dye staining, ophthalmoscopy and biomicroscopic procedures (Oliver, 2003). Management of corneal ulcer firstly requires elimination of underneath etiology and therapy is focussed on avoiding bacterial infection, alleviating the discomfort of eye due secondary uveal spasm, and preventing self-injury (Mary, 2011).